Interaction between the parasitic barnacle Polyascus planus (Cirripedia: Rhizocephala) and its brachyuran host Metopograpsus thukuhar during the development of the externa of the parasite: Control of the gonadal development and vitellogenin synthesis of the host - Chen, Hsiang-Yin; Lee, Chien-Hsun; Tsai, Chih-Cheng; Liu, Hung-Chang; Yang, Su-Ling; Lee, Chi-Ying (Frontiers in Marine Science, 2022)
Developmental profile of the female reproductive apparatus (the externa) of Polyascus planus parasitizing the thukuhar shore-crab Metopograpsus thukuhar is described. The development is divided into 4 stages, which are named based on the distinct color of the externa at each stage. The effects of parasitism on the gonad and hepatopancreas of the host were then examined. The ovary was heavily infiltrated by the rootlet of the parasite, with the oocytes being arrested at the pre-vitellogenic state, whereas the testis, not being infiltrated, still contained abundant amounts of spermatozoa. The hepatopancreas of the hosts of both sexes was heavily infiltrated by the rootlets. Regarding the synthesis of vitellogenin (Vg), the hemolymph precursor of the major yolk protein (vitellin, Vn), expression of host Vg gene was detected in the ovary and hepatopancreas of both non-parasitized and parasitized females, and, importantly, its expression found to be induced in the hepatopancreas of parasitized males. Furthermore, results of quantitative gene expression assays showed that expression levels of the host Vg in the ovary and hepatopancreas did not change significantly among the various parasitization status (i.e., host bearing externa of different developmental stages), nor did those of the parasite Vg in the externa among the developmental stage of the externa. The Vg expression levels in the hepatopancreas of parasitized males and in the externa were however negatively correlated. Finally, analysis of tryptic peptide fragments derived from hemolymph proteins of high molecular weight in the parasitized males confirmed the induction of synthesis of the host Vg, whereas analysis of externa proteins of similar molecular weight revealed that Vg of both host and parasite origins contributes to the formation of parasite Vn. The combined results indicate that the parasitized hosts, regardless of sex, synthesize Vg for the ovarian maturation of the parasite, to which Vg of parasite origin also contributes. Discussion is also made with regard to the strategy the parasite adopts toward hosts of different sexes. The profile of the development of externa established would serve as a temporal framework against which studies of host/parasite interaction can be conducted in a developmental context.